Weather Impacts On Natural, Social And Economic System (WISE) Part I: Sectoral Analysis of Climate Impacts in Italy - Marzio Galeotti; Alessandra Goria; Paolo Mombrini; Evi Spantidaki (Fondazione Eni Enrico Mattei (FEEM), 2004)
This paper focuses on the results of the research work carried out by Fondazione Eni Enrico Mattei (FEEM) within the WISE project. This project aims at investigating the effects and the impacts of extreme weather events, particularly very warm summers, mild winters and storms, on the socio-economic systems of European countries. The output consists of a series of empirical studies, both of quantitative and qualitative-descriptive nature. The work of FEEM in the WISE project covers the quantitative analysis of the impacts of climate extremes on the socio-economic system in Italy and the analysis of individuals' perception of climate extremes based on results from individuals' surveys. In this paper is presented the statistical modelling of the impact of weather, through quantitative analysis of activity time series. In particular, the core sectors analysed include fires, health, energy use, tourism and agriculture.
Keywords: Q2; Q25; 330; Climate change; Extreme events; Impacts; Klimawandel; Katastrophe; Umweltbewertung; Branche; Schätzung; Italien; Wetter; Wirkungsanalyse